Situating Social Practices in Community Energy Projects Three Case Studies about the Contextuality of Renewable Energy Production - Pohlmann, Angela (Energiepolitik und Klimaschutz. Energy Policy and Climate Protection,, 2018)
Angela Pohlmann analyses the social embeddedness of renewable energy production. The author challenges tendencies in the existing literature to homogenize community energy projects. Energy production instead is analyzed as an outcome of complex situations within which dynamic negotiation processes unfold. By combining Theodore Schatzki's practice-theoretical approach with Adele Clarke's situational analysis the focus is shifted from practices as stabilized and routinized forms of human behavior onto their dynamic and negotiated character. Contents State of the Art: Community Energy Projects Theoretical Framework: Combining Practice Theory and Situational Analysis 'A Vehicle to Serve the Community': Analyzing the Comrie Development Trust 'Vom Wut- zum Mutbürger': Analyzing the Kultur-und-Energie-Bunker-Altona Project 'A Symbol for Renewable Energy Production in the City': Analyzing the International Building Exhibition Hamburg Target Groups Academics, researchers, and students in the fields of sociology and cultural anthropology Politicians in the fields of renewable energy production and climate protection The Author Angela Pohlmann is a research assistant at the University of Hamburg, Faculty for Economic and Social Sciences. Her scientific interests include methods and methodologies of qualitative social research, situational analysis, practice theories, and social research on climate change and community energy.